Targeting the Bacterial Protective Armour; Challenges and Novel Strategies in the Treatment of Microbial Biofilm - Kamaruzzaman, Nor Fadhilah; Li, Peng Tan; Mat Yazid, Khairun Anisa; Ibrahim Saeed, Shamsaldeen; Hamdan, Ruhil Hayati; Siew, Shean Choong; Weng, Kin Wong; Alexandru, Chivu; Gibson, Amanda Jane (2018)
Infectious disease caused by pathogenic bacteria continues to be the primary challenge to humanity. Antimicrobial resistance and microbial biofilm formation in part, lead to treatment failures. The formation of biofilms by nosocomial pathogens such as Staphylococcus aureus (S. aureus), Pseudomonas aeruginosa (P. aeruginosa), and Klebsiella pneumoniae (K. pneumoniae) on medical devices and on the surfaces of infected sites bring additional hurdles to existing therapies. In this review, we discuss the challenges encountered by conventional treatment strategies in the clinic. We also provide updates on current on-going research related to the development of novel anti-biofilm technologies. We intend for this review to provide understanding to readers on the current problem in health-care settings and propose new ideas for new intervention strategies to reduce the burden related to microbial infections.